Domy przejściowe w norweskim systemie penitencjarnym – aspekty normatywno-praktyczne - Grzesiak, Sławomir (Wydawnictwo Uniwersytetu Wrocławskiego, 2023)
Halfway houses in the Norwegian penitentiary system have been operating for over twenty years. In recent years, this type of solution has become popular in Bulgaria, the Czech Republic, Slovakia, Romania, Lithuania, and Poland, thanks to EEA grants. Bearing in mind the different legal, social and cultural orders of the indicated countries, the need for optimizing the process of social support for people leaving penitentiary units necessitates educating them about the conditions for the functioning of Norwegian halfway houses. This will avoid possible adaptation and implementation problems in creating analogous solutions in Poland. The study raises the issue of the location of transitional houses, the procedures for qualifying and directing convicts to this type of institution, organization and functioning, as well as the procedures of conduct in Norwegian halfway houses. The raised issues are part of the scientific discourse on the need to conduct research on the effectiveness of the process of implementing halfway houses to Polish legal and social conditions.
Keywords: Prison Service; social readaptation; classification of convicts; dynamic security; small-scale detention